2005
DOI: 10.1107/s1600536805021343
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum dimagnesium

Abstract: Single crystals of the LaMg2 cubic Laves phase were synthesized by arc melting. The binary LaMg2 compound has been shown to adopt the MgCu2‐type structure. The coordination sphere of the rare earth metal, adopting a site symmetry of , consists only of 12 Mg atoms. The site symmetry of the alkaline earth metal is , giving rise to superimposed distorted MgLa6 and MgMg6 octa­hedra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…LaMg 2 (x Mg = 0.667) has the cF24-MgCu 2 structure with the Fd-3m space group (#227) and a = 8.806Å [52]. Single crystal data was reported by Belgacem et al [53]. Raghavan [54] discussed the stability of LaMg 2 at 673 K. Nayeb-Hashemi and Clark [23] suggested that LaMg 2 forms by a peritectic reaction (liquid + LaMg 3 ↔ LaMg 2 ) at 998 K and decomposes by a eutectoid reaction (LaMg 2 ↔ LaMg + LaMg 3 ) at 1048 K. LaMg 3 (x Mg = 0.75) has the cF16-BiF 3 structure with space group Fm-3m (#225) and lattice constant a = 7.51Å [52].…”
Section: Structures and Known Propertiesmentioning
confidence: 84%
“…LaMg 2 (x Mg = 0.667) has the cF24-MgCu 2 structure with the Fd-3m space group (#227) and a = 8.806Å [52]. Single crystal data was reported by Belgacem et al [53]. Raghavan [54] discussed the stability of LaMg 2 at 673 K. Nayeb-Hashemi and Clark [23] suggested that LaMg 2 forms by a peritectic reaction (liquid + LaMg 3 ↔ LaMg 2 ) at 998 K and decomposes by a eutectoid reaction (LaMg 2 ↔ LaMg + LaMg 3 ) at 1048 K. LaMg 3 (x Mg = 0.75) has the cF16-BiF 3 structure with space group Fm-3m (#225) and lattice constant a = 7.51Å [52].…”
Section: Structures and Known Propertiesmentioning
confidence: 84%